2013
DOI: 10.1016/j.jcdr.2013.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatic heart disease in rural south India: A clinico-observational study

Abstract: a b s t r a c tBackground: Rheumatic heart disease (RHD) is still a public health issue in many countries in the world, and particularly in Southeast Asia. India, for example, contributes 25%e50% of the global burden of RHD. Clinic-based and epidemiological studies on RHD in India have used different methodologies and clinical criteria to estimate RHD burden in India. The present study employs strict clinical criteria, including echocardiography, to estimate RHD prevalence and associated clinical complications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 12 publications
(13 reference statements)
0
10
0
Order By: Relevance
“…Indeed, studies have shown significant differences in the prevalence of RHD, when the WHO diagnostic criteria of 2006 is compared with the WHF criteria of 2012 76 . Also, the WHF diagnostic criteria of 2012 have not been universally accepted 52,53,59 . Consequently, alternative guidelines have been adopted in many countries 115 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, studies have shown significant differences in the prevalence of RHD, when the WHO diagnostic criteria of 2006 is compared with the WHF criteria of 2012 76 . Also, the WHF diagnostic criteria of 2012 have not been universally accepted 52,53,59 . Consequently, alternative guidelines have been adopted in many countries 115 .…”
Section: Discussionmentioning
confidence: 99%
“…This nonuniformity most probably depicts the heterogeneity of the risk factors and presenting population of IE pertaining to their region of study. Incidentally, the prevalence of RHD in India, as documented by various population-based studies in the recent decade, is 5.8–9.7/1000 population [ 28 , 29 ], which arguably is one of the highest in the world. Concurrently, the presence of uncorrected CHD in children less than 15 years in India has been speculated in few studies as 4.2/1000 population [ 30 ], but no systematic data on prevalence among adults was available.…”
Section: Discussionmentioning
confidence: 99%
“…Another prospective study in Germany reported an overall prevalence of AF slightly higher than the Italian study, ie, 28.6% in 692 patients with ischaemic stroke or transient ischaemic attack, with prevalence increasing with age . Hanchate et al reported a similar prevalence of AF in the USA in 2013 (ie, 23% in acute ischaemic stroke patients from 8 states), in 2 European studies (24.6% and 28.6%, respectively) and an Australian study (25%; study population 26 960) . However, the prevalence of AF was reportedly lower in some Asian countries, approximately 10% in China, 5.8%‐6% in India, but higher in Japan (32%) …”
Section: Incidence and Prevalence Of Af In Stroke Patientsmentioning
confidence: 91%
“…Differences in the incidence and prevalence rates between studies is likely dependent on the time the study was conducted, the design (nationwide studies, medical insurance databases etc., retrospective, prospective, cross‐sectional) and the study population (age of patients, urban compared with remote areas as their risk factors may vary, for example the prevalence of rheumatic heart disease is higher in rural populations in India) which in turn effects the quality of data obtained …”
Section: Worldwide Prevalence Of Af By Continentsmentioning
confidence: 99%